Monetary Policy, Bank Bailouts and the Sovereign-Bank Risk Nexus in the Euro Area - Fratzscher, Marcel; Rieth, Malte (Review of Finance, 2019)
Abstract The article analyses the empirical relationship between bank credit risk and sovereign credit risk in the euro area, using a system of simultaneous equations identified through heteroskedasticity. We first confirm a two-way causality between both risks, which amplifies initial credit risk shocks. We also document significant credit risk spillovers between sovereigns and banks in the periphery and the core countries. The article then focuses on the impact of ECB non-standard monetary policy and bank bailout policies. We show that bailouts have reduced both risks. Monetary policy lowered in most but not all cases bank and sovereign risk.